2023
DOI: 10.3389/fimmu.2023.1251517
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin protects against intervertebral disc degeneration via TNF/NF-κB and LRP4 signaling

Qunbo Meng,
Kaiwen Liu,
Zhenchuan Liu
et al.

Abstract: BackgroundIntervertebral disc degeneration (IVDD) is a leading cause of low back pain (LBP). The pathological process of IVDD is associated with inflammatory reactions and extracellular matrix (ECM) disorders. Digoxin is widely used for treating heart failure, and it has been reported to have anti-inflammatory effects.ObjectiveThis study is to investigate the role of digoxin in the pathogenesis of intervertebral disc degeneration as well as the involved molecular mechanism, particularly the potential target pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“… Rajasekaran et al (2020) identified a higher abundance of Oxalobacter in degenerated intervertebral disks. Intervertebral disk degeneration is widely recognized as a crucial factor in the onset and progression of LBP ( Meng et al, 2023 ). Hence, we posit that Oxalobacter might contribute to LBP by potentially inducing intervertebral disk degeneration.…”
Section: Discussionmentioning
confidence: 99%
“… Rajasekaran et al (2020) identified a higher abundance of Oxalobacter in degenerated intervertebral disks. Intervertebral disk degeneration is widely recognized as a crucial factor in the onset and progression of LBP ( Meng et al, 2023 ). Hence, we posit that Oxalobacter might contribute to LBP by potentially inducing intervertebral disk degeneration.…”
Section: Discussionmentioning
confidence: 99%